Guidance services in the elementary school - Hansen, James C. ([Washington, D.C. American Personnel and Guidance Association], 1971)
Describes the services provided by the elementary school counselor to students, teachers, and parents.
Keywords: Counseling in elementary education; Student counselors; Counselor Education